A method for preparing flame-retardant PA66 film and PA66 fiber with high color fastness

By using the mixed melt extrusion method of AM-PA66 masterbatch and PA66 slices in PA66 material, the heterogeneous nucleation and hydrogen bonding of dye molecule AM ​​is used to solve the problem of insufficient dyeing uniformity and flame retardant levels of PA66 material. , achieving high color fastness and excellent flame retardant performance.

CN118852700BActive Publication Date: 2024-12-31JIANGSU NEW HORIZON ADVANCED FUNCTIONAL FIBER INNOVATION CENT CO LTD
View PDF 10 Cites 0 Cited by

Patent Information

Application Number
CN202411349810.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-09-26
Publication Date
2024-12-31
Estimated Expiration
2044-09-26

AI Technical Summary

Technical Problem

The existing PA66 materials have problems of uniformity, poor dyeing depth and fastness during the dyeing process. At the same time, their low limit oxygen index and insufficient flame retardant level limit their application in the field of high flame retardant requirements.

Method used

The mixed melt extrusion method of AM-PA66 masterbatch and PA66 slices was used to prepare dye molecules AM and PA66 salts by physical blending to form flame-retardant PA66 films and fibers with high color fastness, and heterogeneous formation of dye molecules AM Nuclear and hydrogen bond interaction improve dye dispersion and mechanical properties.

Benefits of technology

High color fastness, excellent flame retardant performance and mechanical properties have been achieved, the limit oxygen index reaches 28.8~29.5%, the flame retardant grade reaches UL-94V-0, and the tensile strength and bending strength have been significantly improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118852700B_ABST
    Figure CN118852700B_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of fiber materials, and relates to a method for preparing a flame-retardant PA66 film and a PA66 fiber with high color fastness. The method for preparing the flame-retardant PA66 film and the PA66 fiber with high color fastness is as follows: first, PA66 salt and dye molecule AM ​​are used as raw materials, and AM-PA66 salt is prepared by physical blending method, and then AM-PA66 salt is prepared by solid phase polymerization method to obtain AM-PA66 masterbatch, and finally AM-PA66 masterbatch and PA66 slices are mixed evenly, and melt extruded and then cooled to form a flame-retardant PA66 film with high color fastness; or, finally, AM-PA66 masterbatch and PA66 slices are mixed evenly, and melt extruded and then cooled to form a flame-retardant PA66 film with high color fastness. The product obtained by the present invention not only has high leveling rate, but also improves mechanical properties, and also has good flame retardancy.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of fiber materials and relates to a preparation method of a high color fastness flame retardant PA66 film and PA66 fiber. Background Art

[0002] Polyhexamethylene adipamide (polyamide 66 or PA66) is a high molecular polymer containing amide groups. Its structure is similar to natural protein fibers such as wool and silk. Therefore, it is often dyed with weak acid dyes. In an acidic aqueous solution, the amino groups at the ends of the PA66 molecular chain form ammonia ions, which form ionic bonds with the negative ions ionized from the weak acid dye to achieve dyeing. However, PA66 has the problems of high crystallinity, low content of terminal amino groups in the molecule, and weak interaction with the dye. Therefore, the dyeing fiber has poor levelness, dyeing depth and fastness. And this dyeing method also has problems such as serious environmental pollution and high energy consumption. In addition, the limiting oxygen index of the dyed PA66 is 23%, the flame retardant level is only UL-94V-2, and the dripping phenomenon is serious during the combustion process. Therefore, these shortcomings also limit its application in fields with high flame retardant requirements.

[0003] In order to solve the above problems, the existing technology usually adopts the solution coloring method for coloring. This method is to color PA66 during the polymerization process or spinning process, which saves the dyeing process of traditional PA66. The process is simple and the cost is low. The colored fiber also has excellent leveling and color fastness. In addition, while preparing high-quality solution-dyed PA66, it also reduces the environmental pollution caused by dyeing. It is a green and environmentally friendly coloring technology. Therefore, since the 1970s, the solution coloring technology has been vigorously developed and has become one of the commonly used methods for synthetic fiber coloring. However, the processing temperature of polyamide is high, and the solution coloring method puts higher requirements on the dispersion and temperature resistance of the colorant.

[0004] The preparation process of PA66 mainly includes polymerization, melt spinning and other stages. When the solution coloring method is used for coloring, it is mainly divided into two types: solution coloring in the polymerization stage and solution coloring after polymerization, depending on the stage of colorant addition.

[0005] The coloring of the stock solution in the polymerization stage can be achieved by in-situ polymerization, that is, adding a colorant during the polymerization process of synthesizing PA66 to directly obtain colored PA66. This method is simple in process and low in cost, suitable for mass production, but it is easy to contaminate equipment and difficult to clean. It not only requires the colorant to have good compatibility and dispersibility in the polymer matrix, but also to withstand high temperature and high pressure. Therefore, the selection of colorants is very limited and is rarely used in practice. For example, in Reference 1 (Preparation and Properties of NP Compound Flame-retardant PA66 Resin by In-situ Polymerization [J]. Plastics, 2017, 46), NP compound flame-retardant nylon 66 (PA66) resin was prepared by in-situ polymerization, but the tensile strength, impact strength, flexural strength and flexural modulus of PA66 were significantly reduced.

[0006] Post-polymerization solution coloring can be achieved by solution blending or melt blending.

[0007] The solution blending method is to first dissolve the PA66 resin in an appropriate solvent, then add the colorant and additives, fully stir the solution to make the pigment particles dispersed evenly in the solution, and remove the solvent to prepare the colored PA66. This method is simple to operate and the pigment particles are easy to disperse, but the solvent is toxic and harmful.

[0008] The melt blending method is to first melt the PA66 resin at high temperature, then add the colorant and additives, stir thoroughly to disperse the pigment particles evenly in the PA66 matrix, and prepare the colored PA66 after cooling. This method is simple to operate, has less pollution to the equipment, has a short color change cycle, and the colorant does not need to be resistant to high temperature for a long time, but the viscosity of PA66 is high in the molten state, and the pigment particles are difficult to disperse evenly in the polymer matrix. For example, in document 2 (Research on Surface Modification of Carbon Black and Its Application in PA66 Stock Solution Coloring [D]. Wuxi: Jiangnan University, 2023), PA66 masterbatch made of modified carbon black is used as the colorant, and PA66 film is prepared by melt blending, but its thermal stability and mechanical properties are reduced to varying degrees; for example, in document 3 (Preparation and Performance Characterization of Functional Nylon Fibers [D]. Wuhan: Wuhan Textile University, 2018), polyamide chips and black masterbatch are dried and mixed and melt-spun to prepare fibers. The results show that the fiber morphology of the fiber with added black masterbatch is not significantly changed compared with the fiber without added black masterbatch, but the elongation at break is reduced by 10%.

[0009] Therefore, it is of great significance to study a preparation method of high color fastness flame retardant PA66 film and PA66 fiber with excellent mechanical properties to solve the above problems. Summary of the invention

[0010] The purpose of the present invention is to solve the problems existing in the prior art and provide a method for preparing a flame-retardant PA66 film and PA66 fiber with high color fastness.

[0011] To achieve the above object, the technical solution adopted by the present invention is as follows:

[0012] A method for preparing a high color fastness flame retardant PA66 film, comprising uniformly mixing AM-PA66 masterbatch and PA66 slices, melt-extruding, cooling and molding to prepare a high color fastness flame retardant PA66 film;

[0013] AM-PA66 masterbatch is prepared by solid phase polymerization of AM-PA66 salt;

[0014] AM-PA66 salt is prepared by physical blending method using PA66 salt and dye molecule AM ​​as raw materials;

[0015] The chemical structure of dye molecule AM ​​is

[0016] As the preferred technical solution:

[0017] The method for preparing a high color fastness flame retardant PA66 film as described above has a K / S value of 9.92-10.87, a color difference ΔE of 0-0.45, color fastness to sunlight, color fastness to soaping (staining) and color fastness to dry friction of grade 5, a limiting oxygen index of 28.8-29.5%, a flame retardant grade of UL-94V-0, a tensile strength of 80.2-82MPa, and an impact strength of 3.2-3.5kJ / m 2 The flexural strength is 89.9~91.4MPa, and the flexural modulus is 3.1~3.3GPa.

[0018] In the method for preparing a high color fastness flame-retardant PA66 film as described above, the mass ratio of AM-PA66 masterbatch to PA66 chips is 0.001 to 0.01:1.

[0019] In the method for preparing a high color fastness flame retardant PA66 film as described above, the melt extrusion temperature is 250-270°C.

[0020] The preparation method of the high color fastness flame retardant PA66 film as described above, the preparation process of AM-PA66 salt is: PA66 salt and dye molecule AM ​​are added to ethanol, stirred at a speed of 500-1000 r / min for 1-3 hours, then filtered by a circulating water vacuum pump, and then vacuum dried at a temperature of 80-90° C. to prepare AM-PA66 salt;

[0021] The molar ratio of PA66 salt, dye molecule AM ​​and ethanol is 1:1.05-1.2:100-1000.

[0022] In the method for preparing a high color fastness flame retardant PA66 film as described above, the dye molecule AM ​​is obtained by reacting 2,7-diaminoanthraquinone (CAS: 605-44-7) with cyanuric chloride (CAS: 108-77-0) at 95-120° C. in the presence of an acid binding agent; 2,7-diaminoanthraquinone is used as a chromophore, cyanuric chloride is used as a functional modification group, and the connecting bond of the two parts, the imino group (-NH-), can form an intramolecular hydrogen bond with the cyanuric chloride residue, thereby stabilizing the chemical structure of the dye and improving the molecular rigidity;

[0023] The acid binding agent is trimethylamine, triethylamine or N,N-diisopropylethylamine;

[0024] The molar ratio of 2,7-diaminoanthraquinone, cyanuric chloride and acid binding agent is 1:1.05-1.2:10-20.

[0025] The present invention also provides a method for preparing a PA66 fiber with high color fastness and flame retardant properties, wherein AM-PA66 masterbatch and PA66 chips are uniformly mixed and melt-spinned to obtain the PA66 fiber with high color fastness and flame retardant properties;

[0026] AM-PA66 masterbatch is prepared by solid phase polymerization of AM-PA66 salt;

[0027] AM-PA66 salt is prepared by physical blending method using PA66 salt and dye molecule AM ​​as raw materials;

[0028] The chemical structure of dye molecule AM ​​is

[0029] As the preferred technical solution:

[0030] The method for preparing a high color fastness flame retardant PA66 fiber as described above, the color fastness to sunlight, color fastness to soaping (staining) and color fastness to dry friction of the high color fastness flame retardant PA66 fiber are all level 5, the limiting oxygen index is 29.1-29.8%, the tensile strength is 103.7-115 MPa, and the elongation at break is 31.4%-37.2%.

[0031] In the method for preparing a high color fastness flame retardant PA66 fiber as described above, the mass ratio of AM-PA66 masterbatch to PA66 chips is 0.001 to 0.01:1.

[0032] As described above, the method for preparing a high color fastness flame retardant PA66 fiber, the process parameters of melt spinning are: spinneret aperture 0.3-0.5 mm, winding speed 700-750 m / min, first drafting roller speed 100-120 m / min, and drafting multiple 3.6-4.3.

[0033] The preparation method of the high color fastness flame retardant PA66 fiber as described above, the preparation process of AM-PA66 salt is: PA66 salt and dye molecule AM ​​are added to ethanol, stirred at a speed of 500-1000 r / min for 1-3 hours, then filtered by a circulating water vacuum pump, and then vacuum dried at a temperature of 80-90° C. to prepare AM-PA66 salt;

[0034] The molar ratio of PA66 salt, dye molecule AM ​​and ethanol is 1:1.05-1.2:100-1000.

[0035] In the method for preparing a high color fastness flame retardant PA66 fiber as described above, the dye molecule AM ​​is obtained by reacting 2,7-diaminoanthraquinone with cyanuric chloride at 95-120° C. in the presence of an acid binding agent;

[0036] The acid binding agent is trimethylamine, triethylamine or N,N-diisopropylethylamine;

[0037] The molar ratio of 2,7-diaminoanthraquinone, cyanuric chloride and acid binding agent is 1:1.05-1.2:10-20.

[0038] Invention mechanism:

[0039] The dye molecule AM ​​plays a role in heterogeneous nucleation. The addition of dye molecule AM ​​provides more nucleation points, the nucleation frequency is accelerated, and the number of grains increases. However, since the dye molecule AM ​​can form hydrogen bond interactions with the carbonyl group in PA66, and its particle size is large, it is not easy to form large aggregates, thereby improving the dispersibility of the dye molecule AM, the number of nucleation points is larger, and the size of the induced spherulites is greatly reduced within a certain spatial range. In addition, the carbonyl group and imino group in the dye molecule AM ​​can form hydrogen bonds with the imino group and carbonyl group in the PA66 molecule, and the Cl in the dye molecule AM ​​can form halogen bonds with the imino group in the PA66 molecule, which enhances the intermolecular interaction between AM and PA66. Based on the orientation of hydrogen bonds and halogen bonds, the color fastness and dyeing uniformity of the flame-retardant PA66 film and flame-retardant PA66 fiber are improved.

[0040] The modified PA66 is flame-retardant through the joint action of the gas phase and the condensed phase, so that the flame-retardant PA66 film and flame-retardant PA66 fiber have excellent flame-retardant properties. Among them, the flame-retardant mechanism of the dye molecule AM ​​is the synergistic flame retardancy of the gas phase and the condensed phase - 1) decomposed into melamine and cyanuric acid through "sublimation endothermicity", reducing the surface temperature of the polymer; decomposition produces non-flammable gases such as water and ammonia, diluting the oxygen concentration and inhibiting combustion; catalyzing the degradation of PA66 into oligomers and taking away heat in the form of molten droplets. 2) PA66 decomposes under heat to produce Cl· free radicals, which further react to produce phosphoric acid, pyrophosphoric acid, etc., promote the dehydration and carbonization or cross-linking of PA66, and hinder the exchange of heat and oxygen; in addition, Cl· free radicals can also capture free radicals such as HO· that participate in the free radical chain reaction during the combustion process to terminate the combustion reaction.

[0041] The flame retardant PA66 film and flame retardant PA66 fiber prepared by the method of the present invention have significantly improved mechanical properties. First, since the dye molecule AM ​​makes the polyamide molecular chains have larger van der Waals force and more hydrogen bonding, the gap and distance between the polyamide molecular chains are increased, the stretchability of the molecular chain / fiber is changed, and higher mechanical properties are obtained; and the reason for having larger van der Waals force and more hydrogen bonding is that: the van der Waals force is related to the molecular weight, the larger the molecular weight, the larger the van der Waals force, the dye molecule AM ​​reacts to the PA66 chain, increases the molecular weight, and thus increases the van der Waals force; the dye molecule AM ​​has a carbonyl group and an imino group in the structure, which can be used as a hydrogen bonding site to form a hydrogen bond; second, since the dye molecule AM ​​has high dispersibility and does not produce agglomerates, the dye molecule AM ​​acts as a nucleating agent in the system, which increases the crystallinity of the fiber and refines the grains, thereby improving the mechanical properties.

[0042] Beneficial effects:

[0043] (1) The present invention provides a method for preparing a high color fastness flame retardant PA66 fiber, wherein the modified PA66 is flame retardant through the combined action of gas phase and condensed phase, so that the flame retardant PA66 film and the flame retardant PA66 fiber have excellent flame retardant properties.

[0044] (2) A method for preparing a high color fastness flame retardant PA66 fiber of the present invention, wherein the dye molecule AM ​​enables the polyamide molecular chains to have a larger van der Waals force and more hydrogen bonding effects, thereby increasing the gap and distance between the polyamide molecular chains, changing the stretchability of the molecular chains / fibers, and obtaining higher mechanical properties; in addition, the dye molecule AM ​​can form hydrogen bond interactions with the carbonyl group in PA66, and its particle size is large and it is not easy to form large aggregates. When the dye molecule AM ​​acts as a nucleating agent in the system, it will also increase the crystallinity of the fiber and refine the grains, thereby improving the mechanical properties.

[0045] (3) The high color fastness flame retardant PA66 fiber and high color fastness flame retardant PA66 film prepared by the present invention not only have a high level dyeing rate, but also have improved mechanical properties, and also have good flame retardancy. BRIEF DESCRIPTION OF THE DRAWINGS

[0046] Figure 1 It is a schematic diagram of the preparation process of the dye molecule AM ​​and AM-PA66 masterbatch of the present invention. DETAILED DESCRIPTION

[0047] The present invention will be further described below in conjunction with specific embodiments. It should be understood that these embodiments are only used to illustrate the present invention and are not intended to limit the scope of the present invention. In addition, it should be understood that after reading the content taught by the present invention, those skilled in the art can make various changes or modifications to the present invention, and these equivalent forms fall within the scope limited by the appended claims of the application equally.

[0048] The testing methods of the relevant performance indicators in the following embodiments and comparative examples are as follows:

[0049] K / S value and color difference: the K / S value, L*, a*, and b* values ​​of the high color fastness flame retardant PA66 film prepared in each embodiment were tested under a D65 light source and a 10° viewing angle using a colorimeter, and the color difference △E was calculated according to the calculation formula. Five points were randomly tested on each high color fastness flame retardant PA66 film, and the results were averaged. The calculation formula for the color difference △E was: Where, ΔL * is the brightness change; Δa * is the change of redness and greenness; Δb * It is a change in yellow-blueness.

[0050] Color fastness to sunlight: The high color fastness flame retardant PA66 film and high color fastness flame retardant PA66 fiber prepared in each embodiment were tested with reference to GB / T 8426-1998 "Textiles - Tests for Color Fastness - Color Fastness to Light - Daylight".

[0051] Color fastness to washing with soap: The high color fastness flame retardant PA66 film and high color fastness flame retardant PA66 fiber prepared in each embodiment were tested with reference to GB / T 3921-2008 "Textiles - Tests for Color Fastness - Color Fastness to Washing with Soap".

[0052] Color fastness to dry rubbing: The high color fastness flame retardant PA66 film and high color fastness flame retardant PA66 fiber prepared in each embodiment were tested with reference to GB / T 3920-2008 Textiles - Tests for Color Fastness - Color Fastness to Rubbing.

[0053] Color fastness to perspiration: The high color fastness flame retardant PA66 film and high color fastness flame retardant PA66 fiber prepared in each embodiment were tested with reference to GB / T 3922-2013 "Textiles - Tests for Color Fastness - Color Fastness to Perspiration".

[0054] Limiting oxygen index: The high color fastness flame retardant PA66 film and high color fastness flame retardant PA66 fiber prepared in each embodiment were measured with reference to GB / T 2406-2009 standard, and the sample size was 80 mm×10 mm×4 mm.

[0055] Flame retardant grade: The high color fastness flame retardant PA66 films prepared in various embodiments were tested with reference to the vertical burning test in GB / T 2408-2008 standard.

[0056] Tensile strength: The high color fastness flame retardant PA66 film and high color fastness flame retardant PA66 fiber prepared in each example were measured with reference to ISO 527-4 standard.

[0057] Elongation at break: The high color fastness flame retardant PA66 film and high color fastness flame retardant PA66 fiber prepared in each embodiment were measured with reference to GB / T 3923.1-2013 standard.

[0058] Impact strength: The high color fastness flame retardant PA66 film prepared in each embodiment was measured with reference to ISO 180-00 standard.

[0059] Bending strength: The high color fastness flame retardant PA66 film prepared in each example was measured with reference to ISO 178-2010 standard.

[0060] Flexural modulus: The high color fastness flame retardant PA66 films prepared in various embodiments were measured with reference to GB / T 9341-2008 standard.

[0061] Example 1

[0062] A method for preparing a high color fastness flame retardant PA66 film, the steps are as follows:

[0063] (1) preparing dye molecule AM;

[0064] like Figure 1 As shown, in the presence of trimethylamine, 2,7-diaminoanthraquinone and cyanuric chloride in a molar ratio of 1:1.05 are reacted at 95°C to obtain a dye molecule AM, whose chemical structure is Wherein, the molar ratio of 2,7-diaminoanthraquinone, cyanuric chloride and trimethylamine is 1:1.05:10;

[0065] (2) preparing AM-PA66 salt;

[0066] PA66 salt and dye molecule AM ​​were added to ethanol, stirred at a speed of 500 r / min for 1 hour, then filtered by a circulating water vacuum pump, and then vacuum dried at a temperature of 90° C. to prepare AM-PA66 salt; wherein the molar ratio of PA66 salt, dye molecule AM ​​and ethanol was 1:1.05:100;

[0067] (3) Preparation of AM-PA66 masterbatch;

[0068] like Figure 1 As shown, the AM-PA66 salt is transferred to a high-temperature and high-pressure polymerization reactor and purged with nitrogen for 90 minutes, then heated to 175°C for reaction for 2 hours, then evacuated to -0.01MPa, and heated to 220°C for reaction for 30 minutes. Finally, after nitrogen is pressurized to 0.4MPa at 260°C, the melt is directly extruded, and then water-cooled, dried, and sliced ​​to form AM-PA66 masterbatch.

[0069] (4) AM-PA66 masterbatch and PA66 chips with a mass ratio of 0.001:1 were mixed evenly, melted at 250°C by a micro twin-conical screw extruder, and then co-extruded and cast by a connector and a die to obtain a high color fastness flame-retardant PA66 film.

[0070] The K / S value of the finally obtained high color fastness flame retardant PA66 film is 9.92, the color difference △E is 0, the color fastness to sunlight, soap washing and dry friction are all level 5, the color fastness to sweat is level 4, the limiting oxygen index is 28.8%, the flame retardant grade is UL-94V-0, the tensile strength is 80.2MPa, and the impact strength is 3.2kJ / m 2 , the flexural strength is 89.9MPa and the flexural modulus is 3.1GPa.

[0071] Example 2

[0072] A method for preparing a high color fastness flame retardant PA66 film, the steps are as follows:

[0073] (1) preparing dye molecule AM;

[0074] In the presence of triethylamine, 2,7-diaminoanthraquinone reacts with cyanuric chloride at 105°C to obtain the dye molecule AM, whose chemical structure is Wherein, the molar ratio of 2,7-diaminoanthraquinone, cyanuric chloride and triethylamine is 1:1.2:20;

[0075] (2) preparing AM-PA66 salt;

[0076] PA66 salt and dye molecule AM ​​were added to ethanol, stirred at a speed of 800 r / min for 2 hours, then filtered by a circulating water vacuum pump, and then vacuum dried at a temperature of 85° C. to prepare AM-PA66 salt; wherein the molar ratio of PA66 salt, dye molecule AM ​​and ethanol was 1:1.2:1000;

[0077] (3) Preparation of AM-PA66 masterbatch;

[0078] The AM-PA66 salt was transferred to a high-temperature and high-pressure polymerization reactor and purged with nitrogen for 50 minutes, then heated to 180°C for reaction for 3 hours, then evacuated to -0.02MPa, and heated to 225°C for reaction for 60 minutes. Finally, the melt was directly extruded at 280°C after nitrogen was pressurized to 0.5MPa, and then water-cooled, dried, and sliced ​​to form AM-PA66 masterbatch.

[0079] (4) AM-PA66 masterbatch and PA66 chips with a mass ratio of 0.01:1 were mixed evenly, melted at 270°C by a micro twin-conical screw extruder, and then co-extruded and cast by a connector and a die to obtain a high color fastness flame-retardant PA66 film.

[0080] The K / S value of the finally obtained high color fastness flame retardant PA66 film is 10.13, the color difference △E is 0.45, the color fastness to sunlight, soap washing and dry friction are all level 5, the color fastness to sweat is level 4-5, the limiting oxygen index is 29.2%, the flame retardant grade is UL-94V-0, the tensile strength is 80.5MPa, and the impact strength is 3.3kJ / m 2 , the flexural strength is 90.9MPa and the flexural modulus is 3.2GPa.

[0081] Example 3

[0082] A method for preparing a high color fastness flame retardant PA66 film, the steps are as follows:

[0083] (1) preparing dye molecule AM;

[0084] In the presence of N,N-diisopropylethylamine, 2,7-diaminoanthraquinone reacts with cyanuric chloride at 120°C to obtain the dye molecule AM, whose chemical structure is Wherein, the molar ratio of 2,7-diaminoanthraquinone, cyanuric chloride and N,N-diisopropylethylamine is 1:1.12:15;

[0085] (2) preparing AM-PA66 salt;

[0086] PA66 salt and dye molecule AM ​​were added to ethanol, stirred at a speed of 1000 r / min for 3 hours, then filtered by a circulating water vacuum pump, and then vacuum dried at a temperature of 80° C. to prepare AM-PA66 salt; wherein the molar ratio of PA66 salt, dye molecule AM ​​and ethanol was 1:1.12:500;

[0087] (3) Preparation of AM-PA66 masterbatch;

[0088] The AM-PA66 salt was transferred to a high-temperature and high-pressure polymerization reactor and purged with nitrogen for 30 minutes, then heated to 185°C for 4 hours, then vacuumed to -0.01MPa, and heated to 230°C for 45 minutes. Finally, the melt was directly extruded at 270°C after nitrogen was pressurized to 0.6MPa, and then water-cooled, dried, and sliced ​​to form AM-PA66 masterbatch.

[0089] (4) AM-PA66 masterbatch and PA66 chips with a mass ratio of 0.006:1 were mixed evenly, melted at 260°C by a micro twin-conical screw extruder, and then co-extruded and cast by a connector and a die to obtain a high color fastness flame-retardant PA66 film.

[0090] The K / S value of the finally obtained high color fastness flame retardant PA66 film is 10.48, the color difference △E is 0.27, the color fastness to sunlight, soap washing and dry friction are all level 5, the color fastness to sweat is level 4-5, the limiting oxygen index is 29.3%, the flame retardant grade is UL-94V-0, the tensile strength is 81.6MPa, and the impact strength is 3.4kJ / m 2 , the flexural strength is 91.4MPa and the flexural modulus is 3.3GPa.

[0091] Example 4

[0092] A method for preparing a high color fastness flame retardant PA66 film, the steps are as follows:

[0093] (1) preparing dye molecule AM;

[0094] In the presence of triethylamine, 2,7-diaminoanthraquinone reacts with cyanuric chloride at 120°C to obtain the dye molecule AM, whose chemical structure is Wherein, the molar ratio of 2,7-diaminoanthraquinone, cyanuric chloride and triethylamine is 1:1.16:18;

[0095] (2) preparing AM-PA66 salt;

[0096] PA66 salt and dye molecule AM ​​were added to ethanol, stirred at a speed of 700 r / min for 3 hours, then filtered by a circulating water vacuum pump, and then vacuum dried at a temperature of 90° C. to prepare AM-PA66 salt; wherein the molar ratio of PA66 salt, dye molecule AM ​​and ethanol was 1:1.2:100;

[0097] (3) Preparation of AM-PA66 masterbatch;

[0098] The AM-PA66 salt was transferred to a high-temperature and high-pressure polymerization reactor and purged with nitrogen for 70 minutes, then heated to 182°C for 4 hours, then vacuumed to -0.01MPa, and heated to 227°C for 35 minutes. Finally, the melt was directly extruded at 266°C after nitrogen was pressurized to 0.45MPa, and then water-cooled, dried, and sliced ​​to form AM-PA66 masterbatch.

[0099] (4) AM-PA66 masterbatch and PA66 chips with a mass ratio of 0.005:1 were mixed evenly, melted at 255°C by a micro twin-conical screw extruder, and then co-extruded and cast by a connector and a die to obtain a high color fastness flame-retardant PA66 film.

[0100] The K / S value of the finally obtained high color fastness flame retardant PA66 film is 10.87, the color difference △E is 0.16, the color fastness to sunlight, soap washing and dry friction are all grade 5, the color fastness to sweat is grade 5, the limiting oxygen index is 29.5%, the flame retardant grade is UL-94V-0, the tensile strength is 82MPa, and the impact strength is 3.5kJ / m 2 , the flexural strength is 90.9MPa and the flexural modulus is 3.25GPa.

[0101] Example 5

[0102] A method for preparing a flame-retardant PA66 fiber with high color fastness, comprising the following steps:

[0103] (1) preparing dye molecule AM;

[0104] In the presence of N,N-diisopropylethylamine, 2,7-diaminoanthraquinone and cyanuric chloride in a molar ratio of 1:1.13 were reacted at 105°C to obtain the dye molecule AM ​​(chemical formula: ); wherein the molar ratio of 2,7-diaminoanthraquinone, cyanuric chloride and N,N-diisopropylethylamine is 1:1.13:18;

[0105] (2) preparing AM-PA66 salt;

[0106] PA66 salt and dye molecule AM ​​were added to ethanol, stirred at a speed of 800 r / min for 2 hours, then filtered by a circulating water vacuum pump, and then vacuum dried at a temperature of 80° C. to prepare AM-PA66 salt; wherein the molar ratio of PA66 salt, dye molecule AM ​​and ethanol was 1:1.2:100;

[0107] (3) Preparation of AM-PA66 masterbatch;

[0108] The AM-PA66 salt was transferred to a high-temperature and high-pressure polymerization reactor and purged with nitrogen for 30 minutes, then heated to 180°C for 4 hours, then vacuumed to -0.02MPa, and heated to 225°C for 50 minutes. Finally, the melt was directly extruded at 260°C after nitrogen was pressurized to 0.6MPa, and then water-cooled, dried, and sliced ​​to form AM-PA66 masterbatch.

[0109] (4) The AM-PA66 masterbatch and PA66 chips with a mass ratio of 0.004:1 were evenly mixed and melt-spun to obtain high color fastness flame-retardant PA66 fibers;

[0110] The process parameters of melt spinning are as follows: spinneret aperture is 0.3 mm, winding speed is 700 m / min, first drafting roller speed is 100 m / min, and drafting ratio is 3.6.

[0111] The final high color fastness flame retardant PA66 fiber has color fastness to sunlight, color fastness to soaping and color fastness to dry friction of level 5, color fastness to sweat of level 5, limiting oxygen index of 29.8%, tensile strength of 115MPa and elongation at break of 31.4%.

[0112] Example 6

[0113] A method for preparing a flame-retardant PA66 fiber with high color fastness, comprising the following steps:

[0114] (1) preparing dye molecule AM;

[0115] In the presence of triethylamine, 2,7-diaminoanthraquinone and cyanuric chloride in a molar ratio of 1:1.2 were reacted at 95°C to obtain the dye molecule AM ​​(chemical formula: ); wherein the molar ratio of 2,7-diaminoanthraquinone, cyanuric chloride and triethylamine is 1:1.2:20;

[0116] (2) preparing AM-PA66 salt;

[0117] PA66 salt and dye molecule AM ​​were added to ethanol, stirred at a speed of 500 r / min for 1 hour, then filtered by a circulating water vacuum pump, and then vacuum dried at a temperature of 85° C. to prepare AM-PA66 salt; wherein the molar ratio of PA66 salt, dye molecule AM ​​and ethanol was 1:1.05:1000;

[0118] (3) Preparation of AM-PA66 masterbatch;

[0119] The AM-PA66 salt was transferred to a high-temperature and high-pressure polymerization reactor and purged with nitrogen for 50 minutes, then heated to 175°C for reaction for 3 hours, then vacuumed to -0.02MPa, and heated to 220°C for reaction for 60 minutes. Finally, the melt was directly extruded at 280°C after nitrogen was pressurized to 0.5MPa, and then water-cooled, dried, and sliced ​​to form AM-PA66 masterbatch.

[0120] (4) Evenly mixing AM-PA66 masterbatch and PA66 chips at a mass ratio of 0.01:1, and melt spinning to obtain high color fastness flame retardant PA66 fibers;

[0121] The process parameters of melt spinning were as follows: spinneret aperture of 0.5 mm, winding speed of 750 m / min, first drafting roller speed of 120 m / min, and drafting ratio of 4.3.

[0122] The final high color fastness flame retardant PA66 fiber has color fastness to sunlight, color fastness to soaping and color fastness to dry friction of level 5, color fastness to sweat of level 4-5, limiting oxygen index of 29.1%, tensile strength of 103.7MPa and elongation at break of 37.2%.

[0123] Example 7

[0124] A method for preparing a flame-retardant PA66 fiber with high color fastness, comprising the following steps:

[0125] (1) preparing dye molecule AM;

[0126] In the presence of trimethylamine, 2,7-diaminoanthraquinone reacts with cyanuric chloride at 120°C to obtain the dye molecule AM ​​(chemical formula: ); wherein the molar ratio of 2,7-diaminoanthraquinone, cyanuric chloride and trimethylamine is 1:1.05:10;

[0127] (2) preparing AM-PA66 salt;

[0128] PA66 salt and dye molecule AM ​​were added to ethanol, stirred at a speed of 1000 r / min for 3 hours, then filtered by a circulating water vacuum pump, and then vacuum dried at a temperature of 90° C. to prepare AM-PA66 salt; wherein the molar ratio of PA66 salt, dye molecule AM ​​and ethanol was 1:1.12:500;

[0129] (3) Preparation of AM-PA66 masterbatch;

[0130] The AM-PA66 salt was transferred to a high-temperature and high-pressure polymerization reactor and purged with nitrogen for 90 minutes, then heated to 185°C for reaction for 2 hours, then evacuated to -0.01MPa, and heated to 230°C for reaction for 30 minutes. Finally, the melt was directly extruded at 273°C after nitrogen was pressurized to 0.4MPa, and then water-cooled, dried, and sliced ​​to form AM-PA66 masterbatch.

[0131] (4) The AM-PA66 masterbatch and PA66 chips with a mass ratio of 0.001:1 were evenly mixed and melt-spun to obtain high color fastness flame-retardant PA66 fibers;

[0132] The process parameters of melt spinning were as follows: spinneret aperture of 0.4 mm, winding speed of 725 m / min, first drafting roller speed of 110 m / min, and drafting ratio of 4.1.

[0133] The final high color fastness flame retardant PA66 fiber has color fastness to sunlight, color fastness to soaping and color fastness to dry friction of level 5, color fastness to sweat of level 4, limiting oxygen index of 29.4%, tensile strength of 108.6MPa and elongation at break of 34.8%.

[0134] Example 8

[0135] A method for preparing a flame-retardant PA66 fiber with high color fastness, comprising the following steps:

[0136] (1) preparing dye molecule AM;

[0137] In the presence of N,N-diisopropylethylamine, 2,7-diaminoanthraquinone reacts with cyanuric chloride at 112°C to obtain the dye molecule AM ​​(chemical formula: ); wherein the molar ratio of 2,7-diaminoanthraquinone, cyanuric chloride and N,N-diisopropylethylamine is 1:1.18:17;

[0138] (2) preparing AM-PA66 salt;

[0139] PA66 salt and dye molecule AM ​​were added to ethanol, stirred at a speed of 700 r / min for 3 hours, then filtered by a circulating water vacuum pump, and then vacuum dried at a temperature of 90° C. to prepare AM-PA66 salt; wherein the molar ratio of PA66 salt, dye molecule AM ​​and ethanol was 1:1.16:700;

[0140] (3) Preparation of AM-PA66 masterbatch;

[0141] The AM-PA66 salt was transferred to a high-temperature and high-pressure polymerization reactor and purged with nitrogen for 70 minutes, then heated to 183°C for reaction for 3 hours, then evacuated to -0.01MPa, and heated to 228°C for reaction for 40 minutes. Finally, the melt was directly extruded at 270°C after nitrogen was pressurized to 0.5MPa, and then water-cooled, dried, and sliced ​​to form AM-PA66 masterbatch.

[0142] (4) The AM-PA66 masterbatch and PA66 chips with a mass ratio of 0.007:1 were evenly mixed and melt-spun to obtain high color fastness flame-retardant PA66 fibers;

[0143] The process parameters of melt spinning are as follows: spinneret aperture is 0.4 mm, winding speed is 710 m / min, first drafting roller speed is 106 m / min, and drafting ratio is 3.8.

[0144] The final high color fastness flame retardant PA66 fiber has color fastness to sunlight, color fastness to soaping and color fastness to dry friction of level 5, color fastness to sweat of level 5, limiting oxygen index of 29.6%, tensile strength of 112.2MPa, and elongation at break of 32.7%.

Claims

1. A method for preparing a high color fastness flame retardant PA66 film, characterized in that: The AM-PA66 masterbatch and PA66 chips are mixed evenly, melt-extruded and then cooled to form a high color fastness flame-retardant PA66 film; AM-PA66 masterbatch is prepared by solid phase polymerization of AM-PA66 salt; AM-PA66 salt is prepared by physical blending method using PA66 salt and dye molecule AM ​​as raw materials; The chemical structure of dye molecule AM ​​is 2. The method for preparing a high color fastness flame retardant PA66 film according to claim 1, characterized in that: The K / S value of high color fastness flame retardant PA66 film is 9.92-10.87, the color difference △E is 0-0.45, the color fastness to sunlight, soap washing and dry friction are all grade 5, the limiting oxygen index is 28.8-29.5%, the flame retardant grade is UL-94V-0, the tensile strength is 80.2-82MPa, and the impact strength is 3.2-3.5kJ / m 2 The flexural strength is 89.9~91.4MPa, and the flexural modulus is 3.1~3.3GPa.

3. The method for preparing a high color fastness flame retardant PA66 film according to claim 1, characterized in that: The mass ratio of AM-PA66 masterbatch to PA66 chips is 0.001-0.01:

1.

4. The method for preparing a high color fastness flame retardant PA66 film according to claim 1, characterized in that: The melt extrusion temperature is 250-270°C.

5. The method for preparing a high color fastness flame retardant PA66 film according to claim 1, characterized in that: The preparation process of AM-PA66 salt is as follows: PA66 salt and dye molecule AM ​​are added to ethanol, stirred at a speed of 500 to 1000 r / min for 1 to 3 hours, then filtered by a circulating water vacuum pump, and then vacuum dried at a temperature of 80 to 90° C. to prepare AM-PA66 salt; The molar ratio of PA66 salt, dye molecule AM ​​and ethanol is 1:1.05-1.2:100-1000.

6. The method for preparing a high color fastness flame retardant PA66 film according to claim 1, characterized in that: The dye molecule AM ​​is obtained by reacting 2,7-diaminoanthraquinone with cyanuric chloride at 95-120°C in the presence of an acid-binding agent; The acid binding agent is trimethylamine, triethylamine or N,N-diisopropylethylamine; The molar ratio of 2,7-diaminoanthraquinone, cyanuric chloride and acid binding agent is 1:1.05-1.2:10-20.

7. A method for preparing a flame-retardant PA66 fiber with high color fastness, characterized in that: The AM-PA66 masterbatch and PA66 chips are mixed evenly and melt-spun to obtain high color fastness flame-retardant PA66 fibers; AM-PA66 masterbatch is prepared by solid phase polymerization of AM-PA66 salt; AM-PA66 salt is prepared by physical blending method using PA66 salt and dye molecule AM ​​as raw materials; The chemical structure of dye molecule AM ​​is 8. The method for preparing a high color fastness flame retardant PA66 fiber according to claim 7, characterized in that: The color fastness to sunlight, color fastness to soaping and color fastness to dry friction of high color fastness flame retardant PA66 fiber are all grade 5, the limiting oxygen index is 29.1-29.8%, the tensile strength is 103.7-115MPa, and the elongation at break is 31.4%-37.2%.

9. The method for preparing a high color fastness flame retardant PA66 fiber according to claim 7, characterized in that: The mass ratio of AM-PA66 masterbatch to PA66 chips is 0.001-0.01:

1.

10. The method for preparing a high color fastness flame retardant PA66 fiber according to claim 7, characterized in that: The process parameters of melt spinning are: spinneret aperture 0.3-0.5 mm, winding speed 700-750 m / min, first drafting roller speed 100-120 m / min, and drafting multiple 3.6-4.

3.

11. The method for preparing a high color fastness flame retardant PA66 fiber according to claim 7, characterized in that: The preparation process of AM-PA66 salt is as follows: PA66 salt and dye molecule AM ​​are added to ethanol, stirred at a speed of 500 to 1000 r / min for 1 to 3 hours, then filtered by a circulating water vacuum pump, and then vacuum dried at a temperature of 80 to 90° C. to prepare AM-PA66 salt; The molar ratio of PA66 salt, dye molecule AM ​​and ethanol is 1:1.05-1.2:100-1000.

12. The method for preparing a high color fastness flame retardant PA66 fiber according to claim 7, characterized in that: The dye molecule AM ​​is obtained by reacting 2,7-diaminoanthraquinone with cyanuric chloride at 95-120°C in the presence of an acid-binding agent; The acid binding agent is trimethylamine, triethylamine or N,N-diisopropylethylamine; The molar ratio of 2,7-diaminoanthraquinone, cyanuric chloride and acid binding agent is 1:1.05-1.2:10-20.

Citation Information

Patent Citations

  • Active navy blue dye

    CN101760041A

  • Cotton-fiber dye used for supercritical carbon dioxide fluid dyeing and synthetic method thereof

    CN106467676A

  • High-color-fastness low-melting-point polyamide masterbatch preparation method

    CN108410165A

  • Green activated dye based on aminophenylurea system and preparation method and application thereof

    CN108504137A

  • Polyamide color master batch colored by high-content carbon black for spinning and preparation method of polyamide color master batch

    CN114605769A